Bicontinuous Nanophasic Conetworks of Polystyrene with Poly(dimethylsiloxane) and Divinylbenzene: From Macrocrosslinked to Hypercrosslinked Double-Hydrophobic Conetworks and Their Organogels with Solvent-Selective Swelling - Anna Petróczy; István Szanka; András Wacha; Zoltán Varga; Yi Thomann; Ralf Thomann; Rolf Mülhaupt; Laura Bereczki; Nóra Hegyesi; Béla Iván (Gels)
Polymer conetworks, which consist of two or more covalently crosslinked polymer chains, not only combine the individual characteristics of their components, but possess various unique structural features and properties as well. In this study, we report on the successful synthesis of a library of polystyrene-l-poly(dimethylsiloxane) (PSt-l-PDMS) (“l” stands for “linked by”) and polystyrene-l-poly(dimethylsiloxane)/divinylbenzene (PSt-l-PDMS/DVB) polymer conetworks. These conetworks were prepared via free radical copolymerization of styrene (St) with methacryloxypropyl-telechelic poly(dimethylsiloxane) (MA-PDMS-MA) as macromolecular crosslinker in the absence and presence of DVB with 36:1 and 5:1 St/DVB ratios (m/m), the latter leading to hypercrosslinked conetworks. Macroscopically homogeneous, transparent conetworks with high gel fractions were obtained over a wide range of PDMS contents from 30 to 80 m/m%. The composition of the conetworks determined by elemental analysis was found to be in good agreement with that obtained from the 1H NMR spectra of the extraction residues, as a new method which can be widely used to easily determine the composition of multicomponent networks and gels. DSC, SAXS, and AFM measurements clearly indicate bicontinuous disordered nanophase separated morphology for all the investigated conetworks with domain sizes in the range of 3–30 nm, even for the hypercrosslinked PSt-l-PDMS/DVB conetworks with extremely high crosslinking density. The cocontinuous morphology is also proved by selective, composition-dependent uniform swelling in hexane for the PDMS and in 1-nitropropane for the PSt domains. The Korsmeyer–Peppas type evaluation of the swelling data indicates hindered Fickian diffusion of both solvents in the conetwork organogels. The unique nanophasic bicontinuous morphology and the selective swelling behavior of the PSt-l-PDMS and PSt-l-PDMS/DVB conetworks and their gels offer a range of various potential applications.